INSIGHTS INTO THE ETHNOPHARMACOLOGICAL PROPERTIES OF COMBRETUM APICULATUM SOND. (FAMILY COMBRETACEAE): NARRATIVE REVIEW - MAROYI, ALFRED (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Combretum apiculatum sond. is a small to medium-sized deciduous tree which is used in traditional medicine in several countries in tropical Africa. This study was aimed at providing information on the ethnobotany, medicinal uses, phytochemistry, and pharmacological properties of C. apiculatum. Information about ethnobotanical applications, phytochemistry, and pharmacological properties of C. apiculatum was collected from the several online databases such as PubMed®, Google Scholar, ScienceDirect®, Web of Science, SpringerLink®, SciELO, and Scopus®, as well as pre-electronic literature sources which included books, book chapters and other scientific publications obtained from the university library. The findings highlight the use of the bark, fruits, leaves, roots, seeds, stems, and stem bark of C. apiculatum as traditional medicine for bilharzia, conjunctivitis, gastro-intestinal problems, infertility in women, leprosy, respiratory infections, sexually transmitted infections, and skin diseases. Chemical compounds identified from C. apiculatum include amino acids, bibenzyls (dihydrostilbenes), chalcones, flavonoids, phenanthrenes, alkaloids, lignin, phenolics, terpenoids, essential oils, resin acids, lipids, pectins, carboxylated, and hydroxylated polysaccharides. The crude extracts of C. apiculatum exhibited antibacterial, anthelmintic, antifungal, antioxidant, anti-inflammatory, antiproliferative, and cytotoxicity activities. Future studies should focus on detailed ethnopharmacological evaluation of C. apiculatum, particularly its phytochemistry, biological activities, and toxicological assessments, in vivo and clinical studies.